Potensi Penambahan Sludge Minuman Ringan Berkarbonasi untuk Meningkatkan Mutu Kompos - Agustina, I Komang Yudi; Arthagama, I Dewa Made; Trigunasih, Ni Made; Narka, I Wayan; Sumarniasih, Made Sri (Fakultas Pertanian Universitas Udayana, 2024)
Potential Addition of Carbonated Soft Drink Sludge to Improve Compost Quality. This research to aims knowing the dosage mix carbonated soft drink sludge in producing the best quality compost. This research was conducted from January to May 2021 in Tegak Village, Klungkung and at the Soil and Environment Laboratory, Faculty of Agriculture, Udayana University. The design used was a completely randomized design (CRD) with 6 formulation treatments and 4 replications. The treatments included: A (3 kg cow dung + 1 kg rice straw + 0% sludge), B (2,5 kg cow dung + 1,5 kg rice straw + 12,5% sludge), C (2 kg cow dung + 2 kg rice straw + 25 % sludge) D (1,5 kg cow dung + 2,5 kg rice straw + 37,5 % sludge), E (1 kg cow dung + 3 kg rice straw + 50% sludge) and F (0,5 kg cow dung + 3,5 kg rice straw + 62,5% sludge). The results of statistical analysis showed that the treatment tested had a very significant effect on organic C, total N, C/N ratio, P-available, pH and EC but had no significant effect on K-available and water content of the compost produced. The best compost quality was obtained in treatment C (C-organic 31,76%; total N; 1,60%; C/N ratio 19,90; P-available 0,06%; K-available 0,07%; pH 7,47; water content 24,01 %), followed by treatments F (C-organic 23,86%; total N 1,55%, C/N ratio 15,40; P-available 0,04 %; K-avaliable 0,07%; pH 7,68; water content 24,83%) and E (C-organic 26,58%; total N 1,57%; C/N ratio 16,93; P-available 0,05%; K-available 0,07%;pH 7,57; water content 23.36%).